Shifting Up Cutoff Value of D-Dimer in the Evaluation of Pulmonary Embolism: A Viable Option? Possible Risks and Benefits - Raviv, Bennidor; Israelit, Shlomo H. (Emergency Medicine International, 2012)
Objectives. To evaluate the viability of the possibility to use a higher D-dimer value than the one used today in the clinical algorithms evaluating patients suspected to have pulmonary embolism. Methods. A retrospective analysis of 300 serial patients for whom D-dimer values were taken during a 10 month period in the emergency room of a tertiary medical center. Results. Our analysis showed that it may be safe and cost effective to use a D-dimer value of 900 ng/ml rather than the value of 500 ng/ml accepted today, with sensitivity of 94.4%. In younger patients [under 40 years] the sensitivity reached was even higher—100%. Conclusions. Raising cutoff values of D-dimer in screening for pulmonary embolism seems a viable option. There may be a place for “tailoring” cutoff values according individual patient characteristics, such as according age groups. More studies of the subject are warranted.